2018
DOI: 10.1029/2018jb015932
|View full text |Cite
|
Sign up to set email alerts
|

Global and Interregion Characterization of Subduction Interface Earthquakes Derived From Source Time Functions Properties

Abstract: Source time functions (STFs) describe how the seismic moment rate is released with time, and carry information on integral rupture properties, such as static stress drop and radiated energy. In this study, we systematically analyze a set of 1,433 STFs extracted from the SCARDEC method (Vallée and Douet, 2016, https://doi.org/10.1016/j.pepi.2016.05.012), containing the Mw≥5.6, shallow (z≤70 km) earthquakes with dip‐slip mechanism that occurred between 1992 and 2014. At the global scale, STFs properties indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 71 publications
(144 reference statements)
1
17
0
Order By: Relevance
“…However, that location seems to be a poorly coupled area, with low impulsivity and low radiation efficiency sources. In the case of the northern Chilean IDEQs, the margin is almost fully coupled, correlating well with impulsive sources, as suggested by Denolle and Shearer (2016) and Chounet and Vallée (2018). Our results seem to support the constant strain drop model (Vallée, 2013), which could explain most of our data using mainly elastic considerations, without needing to appeal to thermal processes.…”
Section: Geophysical Research Letterssupporting
confidence: 79%
“…However, that location seems to be a poorly coupled area, with low impulsivity and low radiation efficiency sources. In the case of the northern Chilean IDEQs, the margin is almost fully coupled, correlating well with impulsive sources, as suggested by Denolle and Shearer (2016) and Chounet and Vallée (2018). Our results seem to support the constant strain drop model (Vallée, 2013), which could explain most of our data using mainly elastic considerations, without needing to appeal to thermal processes.…”
Section: Geophysical Research Letterssupporting
confidence: 79%
“…Vallée (2013) defines F M as the ratio of moment to duration, which assumes the peak of a triangular function, and found that its depth dependence could be explained with depth variations in elastic properties. The direct measure of the peak of the STF, defined here as A M , also exhibits the depth and moment scaling suggested by Vallée (2013) and Chounet and Vallée (2018).…”
Section: Peak Of Seismic Radiationmentioning
confidence: 82%
“…The analysis of the SCARDEC database may provide clues to the style of seismic radiation during the moment acceleration of earthquakes that may encompass the EDSR. The conclusions that follow on the earthquake growth are contingent on the validity and accuracy of the SCARDEC database, which has provided overall static and dynamic source parameters estimates comparable to global values (Vallée, ; Vallée & Douet, ; Meier et al, ; Chounet & Vallée, ). First, its duration is within the first 10–30% of the total duration.…”
Section: Discussionmentioning
confidence: 99%
“…While this simple law is seismologically observed when considering the whole rupture duration T (i.e. M 0 ∝ T 3 (Bilek et al, ; Chounet & Vallée, ; Houston et al, ; Vallée, )), it is transiently not respected during the development phase. Such breaks in scaling laws have been recently found by other authors (Archuleta & Ji, ; Denolle & Shearer, ).…”
Section: Time Evolution Of the Development Phasementioning
confidence: 99%
“…To do so, we propose to make use of the large catalog of moment rate functions (or source time functions, STFs) provided by the SCARDEC database (Vallée & Douet, 2016). SCARDEC database has first been used Journal of Geophysical Research: Solid Earth 10.1029/2019JB018045 to extract global source properties, such as source-averaged stress/strain drop or rupture velocity (Courboulex et al, 2016;Chounet et al, 2017;Chounet & Vallée, 2018;Vallée, 2013) and is now more and more exploited to characterize the transient parts of STFs (Meier et al, 2017;Melgar & Hayes, 2017;2019). With a similar objective as the studies based on the early stages of the rupture, we will first explore if the moment acceleration in the development phase correlates with the magnitude of the event.…”
Section: Introductionmentioning
confidence: 99%